Challenges in cost modelling of recycling carbon fiber composites - Shehab, Essam; Meiirbekov, Arshyn; Sarfraz, Shoaib (IOS, 2020)
The use of carbon fiber composites (CFCs) has become broad in many industries due to its superior properties compared to conventional materials. However, the increased demand coupled with environmental regulations has led to the development of different recycling methods for CFCs such as mechanical, thermal and chemical processes. Each recycling method has its own requirements and outputs along with some economic implications which need to be justified through cost modelling. This paper aims to identify current challenges associated with cost modelling of different processes for CFC recycling. The main challenges identified are grouped into three main categories such as technical issues, supply chain and market challenges
Keywords: Cost Modelling; Carbon Fibre; Composites